UPAYA MENINGKATKAN KETERAMPILAN KOMUNIKASI SISWA MELALUI METODE COOPERATIVE LEARNING TIPE THINK PAIR SHARE PADA PEMBELAJARAN BAHASA INDONESIA DI KELAS IV SDIT ASY-SYIFA AL-INAYAH 6 KOTA JAMBI. - Dea Putri Meiditya; Sunarto; Nauli Siagian, Fitri (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low communication skills of fourth-grade students at SDIT Asy-Syifa Al-Inayah 6 in Jambi City. This study aims to improve communication skills using the think-pair-share cooperative learning method in Indonesian language learning. The theory used in this study is about the importance of communication skills in facilitating the learning process as proposed by (Tarigan et al., 2023) and the think-pair-share cooperative learning model proposed by (Prasetyawati, 2021). This research is a classroom action research. The subjects of this research are all 19 students of class IV B of SDIT Asy-Syifa Al-Inayah 6 Kota Jambi. This research was conducted in 2 cycles, which included the Planning, Implementation, Observation, and Reflection stages. The research instruments used were teacher observation sheets, student observation sheets, and student communication skills cycle tests. Based on the observation results, it can be seen that the average percentage of teacher activity in cycle I was 73%, increasing to 84% in cycle II. In the student activity observation sheet, the average percentage in cycle I was 67%, increasing to 82% in cycle II. The results of the student communication skills test in cycle I were 63% with an average of 69, increasing in cycle II to 84% with an average of 84. Thus, it can be concluded that there was an increase in communication skills.